Impact of Fish Processing Industrial Effluent on Seaweeds Diversity at Veraval Coastal Area in Gujarat - Ilza Mor; Rutva Dave (International Journal of Scientific Research in Science and Technology, 2024)
The coastal zone is an interface between land and sea. The interaction between land and sea involves physical and chemical processes, which produce characteristic shapes of coast line. Thus, in a coastal zone the terrestrial ecosystem has its influence on the sea and vice versa. Veraval is one of the important port cities located along the western coast of Gujarat in India. The Veraval coast is situated in Gujarat state and its water is polluted by the discharge of Fish processing industry effluent. The intertidal area of Fish processing industry at Veraval coast was selected for the study and the investigation was carried out at Veraval at Lat 210 35’N; Long 690 36E’. Survey was conducted during pre-monsoon, monsoon and post monsoon seasons during the year of 2018. In order to achieve the aims of the present study, following parameters were studied to assess species diversity of seaweeds along increasing distance from the discharge point. Number of seaweed species showed a trend similar to that of species diversity was more related to species richness. Ratio of species number for Green, Brown and Red algae indicated that red algae were in greater proportion than green and brown algae. Seaweed species diversity was minimum near Chemical industry effluent discharge point during post-monsoon, pre-monsoon and monsoon seasons, whereas the diversity increased as the discharge point from the outfall increased.
Keywords: Terrestrial Ecosystem; Chemical Industry; Post-Monsoon; Pre-Monsoon; Monsoon Seasons